Student teachers' perceived knowledge of biological concepts and their performance on biology achievement test - Lucero, Lourdes V. (1984)
A 5-point questionnaire checklist was used to survey perceived knowledge of biological concepts and a 50-item multiple choice test on basic biological concepts was administered to measure actual performance scores. Findings revealed that the respondents perceived themselves strongest in Diversity of Living Things, Cell Structure and Function and Ecology; average or adeequate in Science of Life and Funtioning Organisms; and weakest in Evolution. In actual test performance, Diversity of Living Things was their strongest area. Science of Life, Functioning Organisms and Evolution were rated as weak with Cell Structure and Function and Ecology as very weak areas.
Thesis (M.A.T. Biology)--University of the Philippines, Diliman.
Keywords: Student teachers -- Rating of -- Philippines -- Baguio City (Benguet); Biology -- Study and teaching (Secondary) -- Philippines -- Baguio City (Benguet); Biology teachers -- Training of -- Philippines -- Baguio City (Benguet); Achievement tests -- Philippines -- Baguio City (Benguet); Biology -- Examinations